The aging investor: Insights from neuroeconomics - Peter N. C. Mohr; Hauke R. Heekeren (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Individuals in most industrialized countries have to make investment decisions throughout their adult life span to save for their retirement. These decisions substantially affect their living standards in old age. Research on cognitive aging has already demonstrated several changes in cognitive functions (e.g., processing speed) that likely influence investment decisions. This review brings together research on behavioral and neural aspects of financial decision making and aging to advance knowledge on age-related changes in financial decision making. The dopaminergic system plays a key role in financial decision making, both in financial decisions from description and financial decisions from experience. Importantly, both dopaminergic neuromodulation and financial decision making change during healthy aging. Especially when the parameters of the return distribution have to be learned from experience, older adults show a different and suboptimal choice behavior compared to younger adults. Based on these observations we suggest ways to circumvent the age-related bias in financial decision making to improve older adults' wealth.
Keywords: D03; D87; G02; G11; 330; neuroeconomics; neurofinance; aging; neuromodulation; risk-return models; risk; fMRI; decision making under risk; Anlageverhalten; Altersgruppe; Alte Menschen; Neuroökonomie